Unrestricted funding and nonprofit capacities: Developing a conceptual model - Wiepking, Pamala; Wit, Arjen (Nonprofit management & leadership, 2024)
Unrestricted or flexible funding practices are increasingly popular among funders. There is initial empirical support for the assumption that fewer donor‐imposed restrictions on funding have positive outcomes for nonprofit capacities, including the ability to better deal with external shocks such as presented by the COVID‐19 crisis. However, academic literature on the consequences of donor‐imposed restrictions is scarce, scattered, and lacks an overarching theoretical basis. In this article, we theorize how unrestricted funding may relate to nonprofit capacities and consequently effectiveness. Our theoretical propositions are derived from a review of the academic and gray literature as well as a theory‐based analysis of 20 in‐depth interviews with grantees receiving multi‐year unrestricted funding as a substantial part of their funding portfolio. We propose a conceptual model that hypothesizes how unrestricted funding may affect seven different nonprofit capacities: (1) financial management; (2) operational capacity; (3) staff management; (4) adaptive capacity; (5) strategic planning; (6) mission orientation; and (7) innovation. This framework can function as a much‐needed starting point to support academics and nonprofit leaders to better understand how unrestricted funding relates to nonprofit capabilities and consequently nonprofit effectiveness.